1990
DOI: 10.1210/endo-126-3-1683
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Synthetic Antithyroid Drugs: Iodine Complexation During Oxidation of Iodide

Abstract: A number of compounds of pharmaceutical importance from a variety of chemical families, including thiocyanates, isothiocyanates, thiourea and derivatives, imidazoles, and various amines, were found to form charge transfer complexes with iodine. Parallel studies were carried out to investigate the actions of these drugs on lactoperoxidase and thyroid activity in vivo in the rat (assays of T3 and T4 and histology of the thyroid gland). The results showed that there was a good correlation between the value of Kc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 27 publications
1
43
0
1
Order By: Relevance
“…The reactions were carried out directly in spectrophotometer cuvettes (Hellma 110 QS quartz cells with 1 cm optical path length). The method has been described elsewhere [6,12]. Briefly, the solutions were freshly made up by dilution of stock solution prepared by accurate weighing.…”
Section: Complexation With Iodinementioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were carried out directly in spectrophotometer cuvettes (Hellma 110 QS quartz cells with 1 cm optical path length). The method has been described elsewhere [6,12]. Briefly, the solutions were freshly made up by dilution of stock solution prepared by accurate weighing.…”
Section: Complexation With Iodinementioning
confidence: 99%
“…A wide variety of substances have been found to exert an action on thyroid peroxidase. Some of these molecules have been shown to form charge transfer complexes with molecular iodine in vitro [6]. It has also shown that the formation of these complexes disrupts thyroid metabolism by decreasing the availability of iodine in the gland.…”
Section: Introductionmentioning
confidence: 99%
“…5 So far, various analytical methods in TLC, 6 GC-MS, [7][8] HPLC-UV [9][10][11] or MS [12][13] and CE [14][15] have been described for the effectively monitoring MMZ in kinds of samples including urine, [7][8][9][10][11] plasma, 6 tissues 9,12-13 and serum. 15 Flow injection analysis, 15 electrochemical detec-tion [16][17][18] and molecularly imprinted polymer (MIP) 19 for MMZ are also developed. Among all of these methods, HPLC is the most commonly used method because it is sensitive and selective and it could be provided at a low level of MMZ, but it is expensive and not suitable for extensively prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…From primary studies, it was hypothesised that compounds presenting a high affinity for iodine could induce hypothyroidism [8] by complexing with molecular iodine present in the thyroid, thus leading both to a 'trapping' of molecular iodine by complexation and to an accumulation of the drug in the gland. Thus, the concentration of molecular iodine available for thyroid hormone synthesis (via the I + ion), would be reduced and thyroid hormone levels would decline [9,10]. The best way to demonstrate the proposed mechanism would be to measure the availability of free iodine in the rat thyroid before and after treatment with such drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, only indirect arguments can be looked for to support the hypothesised mechanism. The first one is the already demonstrated relationship between the value of the constant of iodine complexation determined in vitro, of a given drug (Kc) and its activity on thyroid function, [10]: In previous studies dealing with a large number of molecules, it was found that all those characterised by a Kc value higher than 100 litersWmol -1 showed antithyroid effects in rats. A second argument, still not demonstrated, would be the accumulation of these drugs in the thyroid, which is a prerequisite to the proposed mechanism of action.…”
Section: Introductionmentioning
confidence: 99%